Sistem Informasi Peta Dakwah Kader Ikatan Pelajar Muhammadiyah di Kabupaten Garut Menggunakan Metode Rational Unified Process - Baswardono, Wiyoga; Supriatna, Asep Deddy; Hidayattuloh, Yusuf; Arifin, Dudy Mohammad (Institut Teknologi Garut, 2023)
The Muhammadiyah Student Association is a Muhammadiyah student organization which has the aim of da'wah and prepares a generation of students and teenagers who are ready to preach in the way of Islam in accordance with Muhammadiyah's goals. After conducting observations and interviews with the Garut Regency Muhammadiyah Student Association organization, there were problems with data management which was still classified as manual because it used Microsoft Excel so there was no information system for managing cadre data and there was no geospatial system to see the development of the distribution of the Garut Regency IPM da'wah map. Apart from that, there is no disclosure of information on the IPM da'wah map to cadres, so it is difficult for cadres to know the distribution of the da'wah map. The aim of this study is to develop a geographic information system that can be accessed via a web platform, designed for Muhammadiyah Student Association cadres in Garut Regency. The development of this information system follows the Rational Unified Process (RUP) methodology which includes the stages of Inception, Elaboration, Construction and Transition, as well as system modeling using the Unified Modeling Language (UML) which includes use case diagrams, activity diagrams, sequence diagrams and classes diagram. The final result of this study is the existence of a Geographic Information System which is equipped with a map function to access data from various coordinate points. Each coordinate allows the display of information that includes cadre name, coordinates, address and other elements. This system also has the ability to filter data according to the Muhammadiyah Student Association cadre mapping area in Garut Regency, by displaying accurate location information. This aims to support the Regional Leadership of the Garut Regency Muhammadiyah Student Association in analyzing and managing the distribution of cadres based on their zones.